Effects of rubber aggregates on the physical-mechanical, thermal and durability properties of self-compacting sand concrete - Faisal Abdelrahman Hashem Saleh; Nouria Kaid; Kada Ayed; Djamel-Eddine Kerdal; Nadjib Chioukh; Nordine Leklou (Fracture and Structural Integrity)
The aim of this research was to study the effect of incorporating waste rubber aggregates on the physical-mechanical, thermal and durability performance of Self-Compacting Sand Concrete (SCSC) mixtures. Separately, Rubberized Self-Compacting Sand Concretes (RSCSC) were elaborated with three fractions of rubber grains in which natural aggregates were replaced with powder rubber, sand rubber and gravel rubber and four (5, 10, 15 and 20%) addition ratios as volume rates. The performed fresh properties using slump-flow, spreading, t500, sieve stability and air-entrained content tests proved better results for the RSCSC in comparison with reference concretes. Hardened state characterization of the concretes exhibited decreases in the mechanical properties of the RSCSC but the thermal conductivity and the dynamic elastic modulus were improved. Assessment of the concretes durability was accomplished through determination of apparent porosity, capillary absorption. Experimental outputs revealed that RSCSC may be used in structural elements of dense reinforcement and complex formwork, which allows promising solution to reduce the impact of waste tyres on the environment and fight pollution